Prosthetic Shoulder Joint Infection by Cutibacterium acnes: Does Rifampin Improve Prognosis? A Retrospective, Multicenter, Observational Study - Helem H. Vilchez; Rosa Escudero-Sanchez; Marta Fernandez-Sampedro; Oscar Murillo; Álvaro Auñón; Dolors Rodríguez-Pardo; Alfredo Jover-Sáenz; Mª Dolores del Toro; Alicia Rico; Luis Falgueras; Julia Praena-Segovia; Laura Guío; et al. (MDPI AG, 2021)
This retrospective, multicenter observational study aimed to describe the outcomes of surgical and medical treatment of C. acnes-related prosthetic joint infection (PJI) and the potential benefit of rifampin-based therapies. Patients with C. acnes-related PJI who were diagnosed and treated between January 2003 and December 2016 were included. We analyzed 44 patients with C. acnes-related PJI (median age, 67.5 years (IQR, 57.3-75.8)); 75% were men. The majority (61.4%) had late chronic infection according to the Tsukayama classification. All patients received surgical treatment, and most antibiotic regimens (43.2%) included β-lactam. Thirty-four patients (87.17%) were cured; five showed relapse. The final outcome (cure vs. relapse) showed a nonsignificant trend toward higher failure frequency among patients with previous prosthesis (OR: 6.89; 95% CI: 0.80-58.90) or prior surgery and infection (OR: 10.67; 95% IC: 1.08-105.28) in the same joint. Patients treated with clindamycin alone had a higher recurrence rate (40.0% vs. 8.8%). Rifampin treatment did not decrease recurrence in patients treated with β-lactams. Prior prosthesis, surgery, or infection in the same joint might be related to recurrence, and rifampin-based combinations do not seem to improve prognosis. Debridement and implant retention appear a safe option for surgical treatment of early PJI.